2014
DOI: 10.1080/15287394.2013.874303
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Lead in Blood and Related Factors Among Blood Donors in the Western Amazon, Brazil

Abstract: The aim of this study was to (1) determine the reference value of blood lead levels (BLL) in a sample of blood donors of Rio Branco, the capital city of Acre, in the Western Brazilian Amazon, and (2) explore factors influencing lead (Pb) exposure levels. Between 2010 and 2011, blood samples were collected from universal blood donors attending the Central Hemotherapic Unit in Rio Branco with a total number of 1196. Information on characteristics of 1183 donors was obtained through questionnaires. Blood Pb conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
3
15
0
1
Order By: Relevance
“…Our results confirm the association seen in previous studies between BLLs and many risk factors including place of residence, education level, tobacco use, alcohol consumption, and high‐risk lead exposure from occupational and leisure activities . The percentage of BLL variance explained by the variables included in our study (41.1%) is higher compared with other studies . This finding suggests that our study was well designed to identify the significant predictive variables of lead levels among the blood donor population.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results confirm the association seen in previous studies between BLLs and many risk factors including place of residence, education level, tobacco use, alcohol consumption, and high‐risk lead exposure from occupational and leisure activities . The percentage of BLL variance explained by the variables included in our study (41.1%) is higher compared with other studies . This finding suggests that our study was well designed to identify the significant predictive variables of lead levels among the blood donor population.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest a very high environmental lead exposure in this population compared with our population of blood donors. Another survey among 1183 blood donors (890 men and 293 women) was performed in 2010 to 2011 in Rio Branco, a nonindustrial city in Brazil . The GM of BLLs was 0.18 µmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean weight was 81 kg for men and 68 kg for women. Characteristics of study population related to lifestyle and occupations have been previously described (Freire et al, 2014) and are shown in Supplemental material (Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 99%